VALIDASI METODE PENENTUAN SAKARIN MENGGUNAKAN KROMATOGRAFI CAIR KINERJA TINGGI - Agus Kembaren; Tiasina Harahap (Pascasarjana Universitas Negeri Medan, 2014)
Abstract. This research was aimed to validation analytical method of Saccarine and to determine saccarine consentration in soft drink High Performance Liquid Chromatography. Sodium Saccarine salts are used as standard. Sodium Saccarine salts dissolve in mobile phase methanol : fosfat buffer (60:40). Concentration of standard saccarine solution made in 20, 40, 60, 80, and 100 ppm. HPLC Agilent Technology 1260 Infinitely Series, Poroshell/C18 column- 50 mm lenght- id 4.6 mm - particles size 2.7 µm, UV-detector in λ 265 nm, injection volume 20 µL , and flow rate 1 mL/minutes were used in this research. Method validation parameters were determined by linierity, precision, accuracy, LOD, LOQ, and selectivity. The results show that lineariy with R = 0.998702, precision with RSD = 0.192%, accuracy with % recovery = 100.26%, LOD = 0.172 ppm, LOQ = 0.573, and selectivity with Rs = 0.2. Testing for the ‘Sprite Zero’ soft drink show that 117.6 mg/kg saccarine (under the maximum content in carbonated/noncarbonated soft drink). Conclution from this research is, HPLC method can use in analysis saccarine content in soft drink Kata kunci: metode penentuan, sakarin, kromatografi kinerja tinggi